2008
DOI: 10.1215/00031283-2008-021
|View full text |Cite
|
Sign up to set email alerts
|

The Low-Back Merger in the Steel City: African American English in Pittsburgh

Abstract: This article investigates the status of the low-back vowels in African American English in Pittsburgh, Pennsylvania, where the vowels have been merged since at least the late 1800s. The low-back merger is currently spreading across much of the United States, but to date, its incidence in African American speech has been found to be limited. This article draws from a sample of 34 African Americans native to Pittsburgh. Using data from a word list along with an acoustic analysis of the low-back vowels in convers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 31 publications
(38 reference statements)
0
10
0
Order By: Relevance
“…Thus, interactions between African Americans' and whites' speech and ideas about speech have largely escaped scholarly notice. Eberhardt (2008) shows, however, that Pittsburgh African Americans do in fact share one phonological feature (the merger of the low back vowels /A/ and /O/) with white Pittsburghers and not with African Americans elsewhere, and my research shows that Pittsburgh African Americans use a number of lexical items common to local whites but not to African Americans in other cities. 4.…”
Section: Notesmentioning
confidence: 57%
“…Thus, interactions between African Americans' and whites' speech and ideas about speech have largely escaped scholarly notice. Eberhardt (2008) shows, however, that Pittsburgh African Americans do in fact share one phonological feature (the merger of the low back vowels /A/ and /O/) with white Pittsburghers and not with African Americans elsewhere, and my research shows that Pittsburgh African Americans use a number of lexical items common to local whites but not to African Americans in other cities. 4.…”
Section: Notesmentioning
confidence: 57%
“…Labov (1994: 316) calls the COT-CAUGHT merger 'the largest single phonological change taking place in American English'. It has been analyzed extensively in dialectology (Kurath & McDavid 1961;ANAE), with many studies showing its rapid spread across North America (Labov et al 1972;Herold 1997;Majors 2005;Gordon 2006;Eberhardt 2008). Several studies in the Western states have argued for the presence of merger (e.g.…”
Section: Cot and Caught In San Francisco Englishmentioning
confidence: 99%
“…Although in some other regions scholars have found that African Americans tend not to merge these vowels (e.g. Bernstein 1993), in Pittsburgh, I (Eberhardt 2008) found that African Americans share in this feature of local phonology. An auditory analysis of 19 speakers reading pairs from a word list ( cot/caught and pond/pawned ) revealed that almost all speakers produced no distinction between the words in these pairs, and reported hearing no difference between them.…”
Section: Phonetic and Phonological Featuresmentioning
confidence: 95%
“…An auditory analysis of 19 speakers reading pairs from a word list ( cot/caught and pond/pawned ) revealed that almost all speakers produced no distinction between the words in these pairs, and reported hearing no difference between them. In an analysis of a total of 34 African Americans, I (Eberhardt 2008) examined // and / / acoustically, and found that with the exception of one female speaker in her 50s, these speakers showed no systematic difference between the once distinct word classes. The presence of this feature in Pittsburgh AAE can be attributed to the long‐standing presence of the merger in Western Pennsylvania.…”
Section: Phonetic and Phonological Featuresmentioning
confidence: 99%